Application of One Stop Integrated Services in Improving the Effectiveness of Community Services at the Medan District Attorney - Vania Auziva; Andri Soemitra (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
The One Stop Integrated Service System is an integrated service in a unified process starting from the initial stage to the completion stage, the aim is to provide the best service to people seeking justice. The Medan District Attorney's One Stop Service serves the community in a friendly, clean and comfortable room to provide services. With this PTSP, it is hoped that the community can be served well and make it easier to provide maximum service to justice seekers. With the One Stop Service, as one of the implementation units of the Medan District Attorney, it has service standards, service procedures, and time standards so that the effectiveness and efficiency of the services provided can be measured. The use of PTSP is a form of commitment to improve the quality of services to the community, improve transparency and accountability in services.